(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Refractive errors are the main causes of vision loss in children [1-4]. Uncorrected refractive errors often cause a decrease in visual performance, children’s general development delay, neurosis etc. This requires their well-timed rational correction [5, 6]. The purpose of the study was to present a case report of the effect of spectacle correction on the binocular vision formation.